Dynamic computer simulation and energy absorption of foam-filled conical tubes under axial impact loading - Ahmad, Z. (Elsevier BV, 2009)
This paper treats the dynamic response and energy absorption of aluminum foam-filled conical tubes under axial impact loading using non-linear finite element techniques. The influence of geometrical, material and loading parameters on the impact response is investigated using validated numerical models. Results are quantified in terms of important impact response parameters and indicate that the foam filler stabilizes the crushing process and thus improves the energy absorption capacity. The superior performance of foam-filled conical tubes as impact energy absorbers is evident from the results. The research information generated will be useful in developing guidance towards the design of these devices in impact applications.